On distributed logic simulation using time warp - Bauer, Herbert; Sporrer, Christian; Krodel, Thomas (1992)
Abstract: "In this paper we discuss issues related to distributed logic simulation using the promising Time Warp mechanism based on the Virtual Time paradigm. To overcome the extensive memory requirements of Time Warp, we employ an incremental state saving technique instead of checkpointing; state saving itself requires only a negligible amount of overhead. A new asynchronous algorithm for the determination of Global Virtual Time is presented. The GVT process runs in parallel to the simulation processes and guarantees efficient GVT determination without affecting the ongoing simulation. On the average, less than N messages are needed to calculate a new GVT thereby reducing communication costs for GVT calculation to a minimum. Experimental results obtained with a prototype simulator are included in the paper."
Keywords: Computer simulation; Electronic circuit design